Efektivitas Penggunaan Metode Pembelajaran Demonstrasi di SMK Negeri 4 Pangkep - Purwandira, Ayu; Niswaty, Risma; Darwis, Muhammad (Universitas Negeri Makassar, 2018)
This study aims to determine the effectiveness of the use of demonstration methods in class X archival subjects around it. This study uses a qualitative approach. The informants in this study were 5 (five) people. Data collection is done through observation, interview and documentation techniques. The results of this study indicate that archival subject teachers in State Vocational High School 4 Pangkep in implementing the demonstration method have carried out the preparation stage quite well. In addition to the preparation stage, the implementation phase consists of opening steps and implementation steps. In the opening step the teacher still missed some activities that were enough to influence the course of the demonstration process, therefore the opening step was said to be still not good enough. But this is reversed with the implementation steps that have been done well, the activities in this step are carried out optimally. In the final stage, the end stage, assignment and evaluation are also carried out quite well. So that from the overall assessment results starting from the opening stage, then the implementation phase and finally at the end stage of the demonstration method in the archival subjects of class X at Pangkep State Vocational High School 4 has run quite effectively.Â